Penerapan Media Bantu Matras untuk Meningkatkan Keterampilan Senam Lantai Guling Depan Siswa Kelas V Sekolah Dasar Negeri Maol - Duki, Frederikus; Liunokas, Oded; Wora, Dionisius; Ajito, Timoteus (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The forward roll skill among primary school pupils remains relatively low, as some pupils experience difficulties with the movement sequence, lack flexibility, and feel anxious when performing the movement. This study aims to improve the forward roll skill among Year 5 pupils at Maol State Primary School through the use of an inclined mat as an aid. The study employed the Classroom Action Research (CAR) method, conducted over two cycles, each comprising the planning, implementation, observation, and reflection stages. The research subjects consisted of 25 pupils. Data were collected through observation of pupil activities and forward roll skill tests using a psychomotor assessment rubric, and were subsequently analysed descriptively to assess improvements in learning outcomes across each cycle. The results of the study indicate that the use of the inclined mat was effective in improving students’ forward roll skills. In cycle I, an average score of 73.08 was obtained with a mastery rate of 56%, whilst in cycle II this increased to an average of 78.40 with a mastery rate of 80%, thus exceeding the research target of at least 75% of students achieving the Minimum Mastery Criteria. In addition to improving learning outcomes, the use of the inclined mat also helped to reduce fear and boost students’ confidence when performing the movement